Perceptions and Attitudes of Vocational Students in Using Google Gemini as a Writing Tool - Afrilianto Dwicahyo Nugraha (Universitas Negeri Surabaya, 2025)
This study aims to examine the perceptions and attitudes of vocational high school students majoring in culinary arts toward the use of Google Gemini as an AI-powered tool in writing analytical exposition texts. The research background arises from challenges in writing instruction, including limited time, low motivation, and varied English proficiency. A qualitative descriptive method was used, with data collected through semi-structured interviews involving seven 11th-grade students selected via purposive sampling. The findings revealed that students generally viewed Google Gemini as a helpful and user-friendly tool, especially during the planning and drafting stages. Features such as idea generation, grammar assistance, and paragraph structuring were particularly appreciated. Students’ attitudes reflected the cognitive, affective, and behavioral components. While most students expressed positive feelings like satisfaction and confidence, some raised concerns about overreliance and diminished critical thinking. These findings highlight the need for pedagogical strategies that promote digital literacy and the responsible, ethical use of AI in education.